2008
DOI: 10.1038/bjp.2008.212
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of kinin B1 receptor upregulation in a mouse model of colitis

Abstract: Background and purpose: Kinins are implicated in many pathophysiological conditions, and recent evidence has suggested their involvement in colitis. This study assessed the role of the kinin B 1 receptors in a mouse model of colitis. Experimental approach: Colitis was induced in mice by 2,4,6-trinitrobenzene sulphonic acid (TNBS), and tissue damage and myeloperoxidase activity were assessed. B 1 receptor induction was analysed by organ bath studies, binding assay and reverse transcription PCR. Key results: TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
3
33
0
1
Order By: Relevance
“…The recent experimental study investigated the role of BR1s in TNBS -induced mouse model of colitis showing that that selective, orally active, non -peptide B1R antagonist SSR240612 markedly reduced TNBS -induced colitis e.g. intestinal tissue damage and neutrophil influx (Hara et al, 2008). Importantly this study clarified evidence that TNF -may upregulate B1R expression in TNBS colitis model suggesting that anti-TNF-monoclonal antibodies may in part modulate IBD by regulation of BR1 expression.…”
Section: Kinins and Kinin Receptors In Ibdsupporting
confidence: 50%
“…The recent experimental study investigated the role of BR1s in TNBS -induced mouse model of colitis showing that that selective, orally active, non -peptide B1R antagonist SSR240612 markedly reduced TNBS -induced colitis e.g. intestinal tissue damage and neutrophil influx (Hara et al, 2008). Importantly this study clarified evidence that TNF -may upregulate B1R expression in TNBS colitis model suggesting that anti-TNF-monoclonal antibodies may in part modulate IBD by regulation of BR1 expression.…”
Section: Kinins and Kinin Receptors In Ibdsupporting
confidence: 50%
“…B 1 receptor induction by bacterial lipopolysaccharide (LPS) was inhibited by glucocorticoid pretreatment, cyclooxygenase (COX) blockade, and agents inhibiting the synthesis or action of TNF-␣ (82,84,205,608); moreover, endogenous glucocorticoid hormones were shown to exert a tonic inhibitory control on receptor expression through a NF-B-mediated pathway (78). In a model of experimental colitis in mice, B 1 receptor upregulation depended on de novo protein synthesis, NF-B activation, TNF-␣ production, and inducible NO synthase (iNOS) activity (267). Platelet-activating factor (PAF), a proinflammatory mediator, was shown to upregulate B 1 receptors in the rat skin through a pathway involving neutrophils and a NF-B-TNF-␣-IL-1␤ axis (181, 182).…”
Section: Types and General Features Of Bradykinin Receptorsmentioning
confidence: 99%
“…13 Specific inflamed organ-induced B1R expression and the availability of an orally active B1R antagonist (B1Ra) has made the B1R a potential therapeutic target for the treatment of pathologies related to chronic inflammation, such as atherosclerosis, airway inflammation, diabetic neuropathy, arthritis, and neuropathic pain. 14,15 Indeed, since the work of Gougat et al 16 describing the selectivity of this orally active B1Ra, a number of original in vivo studies have reported its therapeutic potential in inflammatory bowel disease, 17 skin inflammatory diseases, 18 sensory polyneuropathy, 19 and neuropathic pain. 20 The role of the B1R in renal inflammation has been poorly investigated.…”
mentioning
confidence: 99%